National Identity as a Factor of Inter-Cultural Communication - E. A. Volkova (Vestnik MGIMO-Universiteta)
The article deals with the definition and origin of the notions «mentality (identity)» and «national mentality (identity)» focusing on their complex essence. The article names factors that affect the formation of national identity, at the same time pointing out the aspect of human life that the identity itself affects. The notion «national identity» is revealed via its vocabulary definitions. National identity is analyzed as a factor of inter-cultural communication, its role and importance in this communication are also analyzed. One of the objectives of the research is signing out the limits of the concepts «national identity» and «inter-cultural communication» and revealing the conditions of their interaction and mutual dependence. National identity is a complex notion, which complexity lies within the combination of mental and emotional, spiritual elements. This factor adds extra difficulty into understanding, as well as investigating the notion of national identity. Thus it is not rarely ignored in linguistics, international communication, even in teaching languages. However, nowadays, when globalization makes international contacts and communication widely accessible, many people meet unexpected difficulties that derive from ignoring national identity factor. That is why recently it is getting more and more obvious that taking national identity into consideration can be one of the main keys to successful communication at all levels.